P53 mutation and LOH at chromosome 9 in urothelial carcinoma - Beöthe, Tamás; Nagy, Anetta; Kovacs, Gyula (Anticancer research, 2011)
Background: Mutation of the p53 gene has been implicated in the development of carcinoma in situ (CIS) to invasive solid urothelial carcinomas (UC) whereas loss of heterozygosity (LOH) at chromosome 9 has been suggested to plag part in the development of papillary UCs. Patients and Methods: The p53 mutation and LOH at chromosomes 17p13.1 and 9 were analysed in 120 UCs. Tumor and matched normal DNA were used for microsatellite allelotyping of chromosome 17p and the entire chromosome 9. Results: LOH at 17p13.1 was found in each grade and stage of the UCs, but mutation of the p53 occurred only in the highly malignant G3 tumors including papillary pT1G3 UCs. LOH were found at one or more of the seven tumor suppressor gene loci along chromosome 9 in all but two of the UCs with p53 mutation. Conclusion: Mutation of the p53 gene is not a pathway correlated genetic change, but is associated with the increased cell proliferation of G3 UCs.